2019
DOI: 10.3389/fimmu.2019.00982
|View full text |Cite
|
Sign up to set email alerts
|

Mass Cytometry Identifies Distinct Subsets of Regulatory T Cells and Natural Killer Cells Associated With High Risk for Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is characterized by autoimmune destruction of insulin producing β-cells. The time from onset of islet autoimmunity to manifest clinical disease can vary widely in length, and it is fairly uncharacterized both clinically and immunologically. In the current study, peripheral blood mononuclear cells from autoantibody-positive children with high risk for T1D, and from age-matched healthy individuals, were analyzed by mass cytometry using a panel of 32 antibodies. Surface markers were chosen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…It has been recently shown that children with newly diagnosed T1D had reduced frequencies of CD16 + CD56 dim and CD16 − CD56 dim NK cell subsets than HC (32). We have previously reported that multiple autoantibody-positive children, who later progressed to T1D, had higher frequencies of two CD8 + CD16 + CD56 dim NK cell subsets than autoantibody-negative individuals (18). By using the same mass cytometry panel, we found an expansion of activated mature/effector CD8 − CD11c + CD16 + CD56 dim CD69 + HLA-DR − NK cells that expressed IFN-γ in adults with N-T1D.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…It has been recently shown that children with newly diagnosed T1D had reduced frequencies of CD16 + CD56 dim and CD16 − CD56 dim NK cell subsets than HC (32). We have previously reported that multiple autoantibody-positive children, who later progressed to T1D, had higher frequencies of two CD8 + CD16 + CD56 dim NK cell subsets than autoantibody-negative individuals (18). By using the same mass cytometry panel, we found an expansion of activated mature/effector CD8 − CD11c + CD16 + CD56 dim CD69 + HLA-DR − NK cells that expressed IFN-γ in adults with N-T1D.…”
Section: Discussionmentioning
confidence: 80%
“…The antibody panel, stimulation conditions, and intracellular staining used for mass cytometry in this study were optimized and validated as described elsewhere (18). Monoclonal antibodies and reagents are described in detail in Supplementary Table 1.…”
Section: Mass Cytometry Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface markers are the most reliable biomarkers for cell type classification (Cui, et al, 2019;Spitzer and Nolan, 2016). Numerous studies in recent decades have used cell surface markers to isolate and characterize cellular populations with distinct biological functions and have discovered many novel cell types in the process (Ahmed, et al, 2019;Barcenilla, et al, 2019). Recent advancement in single cell RNA sequencing (scRNA-seq) technologies enabled direct cell identity assessment through dissecting single cell gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%